Gut Microbiota-Generated Phenylacetylglutamine and Heart Failure. (16th December 2022) - Romano, Kymberleigh A.; Nemet, Ina; Prasad Saha, Prasenjit; Haghikia, Arash; Li, Xinmin S.; Mohan, Maradumane L.; Lovano, Beth; Castel, Laurie; Witkowski, Marco; Buffa, Jennifer A.; Sun, Yu; Li, Lin; et al.
Abstract : Background: The gut microbiota-dependent metabolite phenylacetylgutamine (PAGln) is both associated with atherothrombotic heart disease in humans, and mechanistically linked to cardiovascular disease pathogenesis in animal models via modulation of adrenergic receptor signaling. Methods: Here we examined both clinical and mechanistic relationships between PAGln and heart failure (HF). First, we examined associations among plasma levels of PAGln and HF, left ventricular ejection fraction, and N-terminal pro-B-type natriuretic peptide in 2 independent clinical cohorts of subjects undergoing coronary angiography in tertiary referral centers (an initial discovery US Cohort, n=3256; and a validation European Cohort, n=829). Then, the impact of PAGln on cardiovascular phenotypes relevant to HF in cultured cardiomyoblasts, and in vivo were also examined. Results: Circulating PAGln levels were dose-dependently associated with HF presence and indices of severity (reduced ventricular ejection fraction, elevated N-terminal pro-B-type natriuretic peptide) independent of traditional risk factors and renal function in both cohorts. Beyond these clinical associations, mechanistic studies showed both PAGln and its murine counterpart, phenylacetylglycine, directly fostered HF-relevant phenotypes, including decreased cardiomyocyte sarcomere contraction, and B-type natriuretic peptide gene expression in both cultured cardiomyoblasts and murine atrial tissue. Conclusions: The present study reveals the gut microbial metabolite PAGln is clinically and mechanistically linked to HF presence and severity. Modulating the gut microbiome, in general, and PAGln production, in particular, may represent a potential therapeutic target for modulating HF. Registration: URL: https://clinicaltrials.gov/ ; Unique identifier: NCT00590200 and URL: https://drks.de/drks_web/ ; Unique identifier: DRKS00020915.